2018
DOI: 10.1016/j.buildenv.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

How do shared-street design and traffic restriction improve urban soundscape and human experience? —An online survey with virtual reality

Abstract: This is a repository copy of How do shared-street design and traffic restriction improve urban soundscape and human experience?-An online survey with virtual reality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 36 publications
0
16
1
1
Order By: Relevance
“…The first of our research objectives was to test the use of virtual models in evaluating design proposals for achieving access to blue spaces (within the size range represented as "urban acupuncture"). Judging by the content of the comments, we found that people participating in the experiment were often willing to look beyond visualisation accuracy, contrary to the feedback received by Jiang et al [59] in their study where the quality of the visualisation and sound was heavily commented. They were also able to judge designs at the real landscape scale and they also showed their understanding of the accommodation capacity of each design.…”
Section: Results In Relation To the Research Objectivescontrasting
confidence: 86%
See 1 more Smart Citation
“…The first of our research objectives was to test the use of virtual models in evaluating design proposals for achieving access to blue spaces (within the size range represented as "urban acupuncture"). Judging by the content of the comments, we found that people participating in the experiment were often willing to look beyond visualisation accuracy, contrary to the feedback received by Jiang et al [59] in their study where the quality of the visualisation and sound was heavily commented. They were also able to judge designs at the real landscape scale and they also showed their understanding of the accommodation capacity of each design.…”
Section: Results In Relation To the Research Objectivescontrasting
confidence: 86%
“…A major concern, still not adequately addressed, is the issue of application in real-life planning and participation situations where VR is used as a tool to define design and planning solutions through informed participation en masse [40,41,[54][55][56]. However, some examples of research where design alternatives have been evaluated with the help of the wider public do exist, covering transportation infrastructure [57][58][59][60][61] solutions and green space planning [62,63]. By developing and presenting different design options in a structured way (where all the variables are controlled) differences between options can be identified as being related to specific aspects of the designs as opposed to random environmental factors (such as the effect of image lighting).…”
Section: Introductionmentioning
confidence: 99%
“…In order to unequivocally state that the idea of the developed system is correct, some research should be carried out to confirm or contradict the thesis that virtual reality can be used in the process of smart designing and evaluating of lighting [49][50][51][52][53][54][55][56][57][58][59][60][61]. Initially, the decision was made to use the indoor scene for testing.…”
Section: Results Of Scientific Visualisations For Virtual Reality and Discussionmentioning
confidence: 99%
“…For visual rendering, many studies used non-HMD options. Some of them adopted non-immersive methods, such as a monitor screen [8,19,45,[67][68][69], visual screen [70] and 2D projection [71,72]. Some of the studies utilized the immersive Cave Automatic Virtual Environment (CAVE) system [65,73].…”
Section: Other Visual Rendering Methodsmentioning
confidence: 99%